Growth and production of ‘Grand Nain’ banana in response to application of simple superphosphate and monoammonium phosphate to an area irrigated with calcareous water - Nascimento, Edinon Manoel; Pacheco, Dilermando Dourado; Silva, Tatiane Carla; Jacome†, Wallison Fagundes; Alcântara, Sérgio Ferreira; Montanari, Rafael (Revista Agrogeoambiental, 2021)
The supply of water of adequate quality for irrigation purposes is becoming increasingly scarce, forcing producers to use restrictive water, such as that with high concentrations of calcium bicarbonate, which is widespread in northern Minas Gerais. This leads to severe chemical imbalances in the soil and in the plants, which significantly reduces the longevity of the farms. The objective of the present work was to evaluate the growth and production of ‘Grand nain’ bananas over a production cycle in response to phosphate fertilization based on simple superphosphate and monoammonium phosphate (MAP) in a soil irrigated with calcareous water. The doses tested were 0, 5, 10, 20, and 30 g P2O5 from simple superphosphate (18 % P2O5) and MAP (48 % P2O5) fertilizers, for a total of nine treatments every three months. Ammonium sulfate and potassium chloride were used in the monthly fertilization, and boric acid, magnesium sulfate, zinc sulfate, and tanned cow dung common to all plants were used in the quarterly fertilization. The results show that the simple superphosphate fertilizer provides a greater productive response of ‘Grand nain’ bananas compared to MAP in most doses tested. Thus, the hypothetical chemical imbalance caused by irrigation with calcareous water and enhanced by the simple superphosphate fertilizer was not observed in the first cultivation cycle of the ‘Grand nain’ banana.